"Immersion in an ocean of psychological tension:" The voices of mothers with children undergoing hemodialysis - Tayebeh Pourghaznein; Abbas Heydari; ZahraSadat Manzari; Najmeh ValizadehZare (Wolters Kluwer Medknow Publications, 2018)
Background: Compared with other renal replacement therapies, hemodialysis treatment can impose restrictions on children with chronic renal failure and their mothers. Such pediatric illness can also lead to negative effects on mothers' physical and mental health. Knowledge about mothers' experiences can aid medical teams to support mothers in playing their roles as care managers. Providing supports to mothers can exert significant effects on mothers' health status and indirectly improve patient outcomes and whole family functioning. This study was aimed at understanding the meanings of care for children undergoing hemodialysis based on mothers' lived experiences. Materials and Methods: This study is a qualitative research using hermeneutic phenomenology. A total of 17 interviews were conducted with 11 mothers of children undergoing hemodialysis. The interview sessions were recorded and transcribed, after which the data were analyzed using van Manen's methodology. Results: The main themes identified in this study was "immersion in an ocean of psychological tension," which suggests that the mothers of the children undergoing hemodialysis are overwhelmed by the numerous psychological pressures that they encounter during their children's treatment. This theme was constituted by the subthemes "bewilderment between hope and despair," "endless concerns," "agony and sorrow," and "a sense of being ignored." Conclusions: The findings indicated the need to implement multilateral support measures that align with the educational, emotional-psychological, and financial needs of mothers with children receiving hemodialysis treatment. Such measures should be taken with the participation of multidisciplinary teams.